2005
DOI: 10.1111/j.1365-2133.2005.06699.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of skin disease following renal transplantation on quality of life

Abstract: The dermatological complications of immunosuppressive therapy are common in RTR and can significantly impair QoL in certain individuals. Visible, infectious and cosmetic skin problems had most impact on QoL while a history of skin cancer had a lesser impact. Early dermatological referral and careful choice of immunosuppression may enhance the QoL, particularly in young and female RTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 17 publications
4
49
0
1
Order By: Relevance
“…Solid organ transplantation, however, carries an increased risk of cancer, and it is significant that the most frequent type of lesions that develop among transplant recipients is NMSC [4]. These represent approximately 40% to 53% of the diagnosed tumors in this group [5] and have a measurable impact upon patient morbidity and quality of life [6]. In a typical European renal transplant population, it is estimated that 1 patient in 5 will develop a neoplastic lesion by 15 years posttransplantation, rising to 2 in 5 by 20 years posttransplantation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Solid organ transplantation, however, carries an increased risk of cancer, and it is significant that the most frequent type of lesions that develop among transplant recipients is NMSC [4]. These represent approximately 40% to 53% of the diagnosed tumors in this group [5] and have a measurable impact upon patient morbidity and quality of life [6]. In a typical European renal transplant population, it is estimated that 1 patient in 5 will develop a neoplastic lesion by 15 years posttransplantation, rising to 2 in 5 by 20 years posttransplantation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients who undergo renal transplantation require long-term immunosuppression and, as such, they are at risk of a number of skin complications. Studies have shown that these dermatological conditions, including dry skin, can have a considerable impact on the patients' quality of life [22] . Dermatological conditions are common in patients who have undergone renal (and other major organ) transplantations.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…However, several studies highlighted an increased risk of developing skin and mucosal lesions in organ transplant patients receiving CspA or FK506 treatment [14], [15]. Under normal condition, re-epithelization of wounds requires keratinocyte migration, proliferation and differentiation.…”
Section: Resultsmentioning
confidence: 99%